The Riddle of Heterarchy: Power Transitions in Cross-Functional Teams - Aime, Federico; Humphrey, Stephen; DeRue, D. Scott; Paul, Jeffrey B. (Academy of Management Journal, 2014)
In this paper, we develop the concept of a power heterarchy, which is a conceptualization of power structures in groups that is more dynamic and fluid than traditional hierarchical structures. Through a study of 516 directional dyads in 45 teams, we demonstrate that heterarchical structures in which the expression of power actively shifts among team members to align team member capabilities with dynamic situational demands can enhance team creativity. Our results indicate that this positive effect of power heterarchies on team creativity is contingent on the team perceiving the shifts in interpersonal power expressions as legitimate. We discuss the implications of this heterarchical power structure for research on group functioning, power, and legitimacy in organizations.